2020
DOI: 10.3866/pku.whxb202011022
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Graphene Quantum Dots Modified BiOI/PAN Flexible Fiber with Enhanced Photocatalytic Activity

Abstract: In environment remediation, photocatalytic oxidation is a promising technique for removing organic pollutants. Compared to adsorption, biodegradation, and chemical oxidation, photocatalytic oxidation can eliminate organic pollutants completely, conveniently, and cheaply in an environmentally friendly manner. Visible-light-driven photocatalytic oxidation is particularly advisable because of the high proportion of visible light energy in solar energy. Bismuth oxyiodide (BiOI) is a promising visible-light-driven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…[52] And natural self-degradation of these massive pollutants is slow and time-consuming. [53] Thus, it is urgent to find a convenient and efficient method to remove these toxic pollutants. Traditional treatment processes may not be suitable for some common pollutants.…”
Section: Environmental Remediationmentioning
confidence: 99%
“…[52] And natural self-degradation of these massive pollutants is slow and time-consuming. [53] Thus, it is urgent to find a convenient and efficient method to remove these toxic pollutants. Traditional treatment processes may not be suitable for some common pollutants.…”
Section: Environmental Remediationmentioning
confidence: 99%
“…Correspondingly, it suggested that the BiOCl in BC2 possessed denser electron cloud. Obviously, partial electrons of Bi 4 O 5 Br 2 transferred to BiOCl after contact, implying formation of internal electric field between their surfaces 41,42,46,47 . In view of the large contact area, this internal electric field may be well dispersed in the large interface and play a significant role in further improvement of photoinduced carrier transfer.…”
Section: Resultsmentioning
confidence: 99%
“… 40 42 As a kind of semiconductor, bismuth oxyhalides (BiOX, X = halogens) belong to the tetragonal crystal system with layered structures composed of X – and [Bi 2 O 2 ] 2+ layers. 43 , 44 Different electric densities between layers lead to orbital polarization, which in turn produces a self-built electric field and further promotes the separation of photoinduced carriers. 45 Among these compounds, BiOBr has attracted extensive interest for its visible-light catalytic activity.…”
Section: Introductionmentioning
confidence: 99%